Isolation and sequence of ctaA, a gene required for cytochrome aa3 biosynthesis and sporulation in Bacillus subtilis. - Mueller, J P (1989)
Cytochrome aa3 is one of two terminal oxidase complexes in the Bacillus subtilis electron transport chain. A novel genetic strategy was devised which permitted the isolation of B. subtilis mutants lacking cytochrome aa3 by selection for streptomycin-resistant clones which failed to oxidize the artificial electron donor N,N,N',N'-tetramethyl-p-phenylenediamine. Two mutations were studied intensively. Spectroscopic examination showed that each mutant lacked cytochrome aa3; they were also asporogenous and unable to grow on lactate as the sole carbon and energy source. These mutations were mapped to a locus designated ctaA, located at 127 degrees between pyrD and metC on the B. subtilis chromosome. Both ctaA mutations were closely linked by transformation to the pycA locus. The ctaA locus and a portion of the pycA locus were cloned from a B. subtilis integration library constructed in Escherichia coli. A recombinant plasmid containing a 4.0-kilobase insert of B. subtilis DNA could transform both ctaA mutants to CtaA+. Gene disruption and complementation experiments with subcloned fragments revealed that the ctaA locus consisted of a single transcriptional unit about 1.35 kilobase pairs in size. The nucleotide sequence of the ctaA transcriptional unit contains a single open reading frame capable of coding for a protein with a predicted molecular weight of 34,065. The predicted protein is extremely hydrophobic, with several probable membrane-spanning domains. No sequence similiarity was found between ctaA and the highly conserved procaryotic and mitochondrial oxidase polypeptides. Cloning and sequence analysis of two ctaA mutations revealed that one allele is a nonsense mutation in the carboxy terminus and the other is a missense mutation in the amino terminus; this indicates that the pleiotropic phenotype conferred by each mutation was caused by loss of CtaA or of its activity. Genetic evidence suggests that the ctaA gene product is required as an accessory protein in the genetic expression, posttranslational biogenesis, or both, of the cytochrome aa3 complex and during an early stage of sporogenesis.